Plant growth-promoting endophytic consortium improved artemisinin biosynthesis via modulating antioxidants, gene expression, and transcriptional profile in Artemisia annua (L.) under stressed environments - Arpita Tripathi; Praveen Pandey; Shakti Nath Tripathi; Alok Kalra (Plant Stress)
Artemisia annua L., an important medicinal plant in traditional Chinese medicine, produces an array of secondary metabolites, most notably artemisinin, a potent anti-malarial phytomolecule. However, its low concentration restricts its supply, necessitating a sustainable approach for increasing in planta artemisinin biosynthesis. The biosynthesis of secondary metabolites in plants relies on a multi-step cellular cascade known to be triggered by linked endophytes. Since no single endophyte can up-regulate every step in the biosynthesis process, we tried a consortium of four endophytes: ART1 (Bacillus subtilis), ART2 (Bacillus licheniformis), ART7 (Burkholderia sp.) and ART9 (Acinetobacter pittii) regulating key artemisinin biosynthesis pathway genes and transcriptional factors (TFs) for attaining maximum artemisinin yield. Intriguingly, all the endophytes inoculated plants showed enhanced growth, greater adaptability, and ability to mitigate environmental stresses, which might be attributed to the improved accumulation of chlorophyll, carotenoid, protein, catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) while reduction in proline and 1-Aminocyclopropane-1-carboxylic acid (ACC) level. Moreover, consortia and ART7 enhanced remarkable biomass in all four environments viz., normal (41.78 %, 29.05 %), drought (62.91 %, 29.37 %), salinity (35.15 %, 23.71 %), and waterlogging (48.37 %, 39.52 %); as well as artemisinin content in normal (51.61 %, 41.16 %), drought (32.87 %, 28.76 %), salinity (25.64 %, 19.23 %), and waterlogging (31.57 %, 28.07 %) compared to control. This stimulation of artemisinin by consortia and ART7 emerged from the up-regulation of major structural genes like CYP7AV1, DXS1, HMGR, DXR1, FPS, ADS, ADH2, SQC, ALDH, HMGS, ADH1, and ISPH while down-regulation of SQS, that enabled the metabolic flux flowed toward artemisinin biosynthesis and were able to disrupt the restricted enzymatic stages in the artemisinin biosynthesis pathway; besides, TFs such as bZIP, AP2, C3H, ARF, E2F, MYB, WRKY, MYC, and ERF modulate gene expression, and these proved as possible candidates for studying adaptation to multiple stress and their mechanisms. In summary, our study reflects the potential of the endophytic consortium for strengthening one endophyte's functional vulnerability with another to gain maximum artemisinin yield and plant tolerance against various stresses via regulating essential metabolic pathway genes.